2017
DOI: 10.2519/jospt.2017.7314
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Management, Rehabilitation, and Functional and Clinical Progression of Osteitis Pubis/Pubic Bone Stress in Professional Soccer Players: A Case Series

Abstract: Study Design Case series. Background Pubic bone stress (PBS) is a common acute or chronic response of the pelvis in sports where sprinting, kicking, twisting, and cutting are the dominant movements. There are few nonoperative rehabilitation strategies for the condition reported in the literature, and the outcome of conservative treatment has not been documented. Case Description Five professional and academy soccer players complaining of pubic symphysis pain, confirmed as PBS on magnetic resonance imaging and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Physiotherapy seems to have been successful for treatment of osteitis pubis in the athletes, and local shock wave therapy significantly reduced pain, thus enabling return-to-play within 3 months of injury 31. McAleer et al32 described a non-operative rehabilitation program for professional and aspiring professional football players with osteitis pubis. Their rehabilitative protocol was based on a specific nine-point program that included pain control, tone reduction of over-active structures, improved range of motion at hips, pelvis and thorax, adductor strength, functional movement assessment, core stability, lumbo-pelvic control, gym-based strengthening and field-based conditioning/rehabilitation.…”
Section: Treatment and Return To Sportmentioning
confidence: 99%
“…Physiotherapy seems to have been successful for treatment of osteitis pubis in the athletes, and local shock wave therapy significantly reduced pain, thus enabling return-to-play within 3 months of injury 31. McAleer et al32 described a non-operative rehabilitation program for professional and aspiring professional football players with osteitis pubis. Their rehabilitative protocol was based on a specific nine-point program that included pain control, tone reduction of over-active structures, improved range of motion at hips, pelvis and thorax, adductor strength, functional movement assessment, core stability, lumbo-pelvic control, gym-based strengthening and field-based conditioning/rehabilitation.…”
Section: Treatment and Return To Sportmentioning
confidence: 99%
“…Nevertheless, Schöberl et al showed the superiority of intensive conservative therapy over the absolute abstention from sports in their level 1 study [10]. Recent studies have emphasized the importance of an individualized, progressive, multimodal rehabilitation program [10,11,25,36]. In the program presented in this study, patients move through the levels after they are able to perform exercises without pain and achieve adequate levels of motion and core stability grading [11].…”
Section: Rehabilitationmentioning
confidence: 79%
“…Youth players suffering from long-standing pubic-related groin pain typically present with nonacute, load-dependent pain over the os pubis or symphyseal gap. Pain can be unilateral or bilateral, and it is typically Eberbach et al BMC Musculoskeletal Disorders (2021) 22:958 exacerbated by running, kicking, hip adduction or flexion, and eccentric loads on the M. rectus abdominis and/ or the adductors [11,25].…”
Section: Diagnostic Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…31 In fact, a recent study demonstrated that a nonoperative rehabilitation program including core stability training reduced pain and allowed return to training in soccer players with pubic stress syndrome with no recurrence after two years. 32 Hip extensors strength predicted increased magnitude of pelvic posterior rotation during the bridge test. Gluteus maximus is a hip extensor that is recruited to maintain hip extension of the support limb during the bridge test.…”
Section: Discussionmentioning
confidence: 95%